THE EFFECT OF ADDITION OF STRAW MASHROOM (Volvariella volvaceae) ON THE CUNSUMER ACCEPTANCE TO THE CATFISH (Clarias gariepinus) GRILLED CAKE - Nasution, putri Silvia Nauba; Dewita, Dewita; Desmelati, Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research aimed to determine the effect of the addition of straw mushroom (Volvariella volvaceae)on the customer acceptance to the catfish(Clarias gariepinus)grilled cake. The method used in this research was experimental method and the design used was non-factorial Randomized Completely Design(RCD). The treatment conducted was addition of the mushroomat varied quantity (0 gs, 100 gs, 200 gs and 300 gs) in the processing of catfishgrilled cake. The results showed that the best catfishgrilled cake was produced by the addition of 200 gs mushroom, shown by the highest acceptance of taste (82.5%), texture (90%), flavor (83.75%) and appearance (81.25%). The product was containing water (52.19%), protein (10.82%), fat (0.09%) and ash (0.85%). The organoleptic characteristics of the product were good tasted, flavored spicy and specify fish meat and mushroom, supple and solidtextured, and yellow colored. Keyword : Clarias gariepinus, Volvariella volvaceae, grilled cake, costumer acceptance